Edukasi Penanganan Cedera Sprain Ankle Pada Atlet Di Unit Kegiatan Mahasiswa Tennis Universitas Muhammadiyah Surakarta - Farid Rahman; Nafi' Ika Salsabella; Gusti Dwi Apriyanto; Muh Anugerah Dzul Kaidah; Shervina Aryan Shifwa Anantha; Wahyu Rizkika Azis; Arif Pristianto (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2023)
Tennis court is a sport that is very popular with the public. Usually, this activity aims to increase achievement and exercise for fitness and health. Endurance and strength are very important components of physical condition. In tennis, athletes often experience musculoskeletal injuries, especially in the extremities. Observations on the field show that one of the injuries that tennis athletes often experience is an ankle sprain. Ankle sprains that occur in tennis players usually occur due to a sudden turn in the ankle with a strong force that causes a tear in the ligament. In an effort to prevent ankle sprains in tennis athletes at UKM Tennis at the Muhammadiyah University of Surakarta, it is necessary to educate the athletes about proper handling of injuries and prevention of recurrence of injuries. Providing education is carried out through counseling methods and using leaflet media. To see the level of success of implementing counseling regarding handling ankle sprain injuries with the exercise therapy method for field tennis athletes at UKM Tennis, Muhammadiyah University of Surakarta, pre-tests and post-tests were given via the Google form before and after the presentation of the material. From the data obtained, the provision of education through counseling and leaflet media has an influence on the knowledge of athletes, although not too significant. The obstacle in implementing this community is the limited time given from the target community.